The fieldwork and control engineering studies on thermal comfort of occupants in a conventional office building in the tropics - Yau, Y.H.; Chang, C.P. (SAGE Publications, 2016)
This paper presents the fieldwork and the control system studies to examine and improve the thermal comfort of the occupants in a typical office building in Malaysia. The proposed control system works as the basis of adjusting the thermostat setting at a certain period of time with the degree of using the fuzzy logic. The thermostat of the central AC system has its set point fixed between 21 and 22 slightly below the range of 23-26 as recommended by Malaysian Standard MS1525. In order to maintain the room comfort, the occupants choose to switch OFF the central AC system for a certain period of time before it is switched back ON. It has been repeated at least once per working days. Therefore, the proposed control system is designed to overcome this practice. Pre- and post-comfort surveys have been conducted where the thermal comfort level of the occupants throughout this study is investigated. The air temperature (Ta), globe temperature (Tg), air velocity (V) and relative humidity (RH) in the occupied area were data-logged for continuous five working days. These data are used to compute the operative temperature (Top) before new thermostat set points are generated, which indicates possible adjustment from the recommended set-point (24). The proposed thermostat setting has an error tolerance of 2.9% or less. As a result, the simulation results show an adjustment of the thermostat setting from 24 to 25.5, which successfully maintained the room temperature of the main office between 23.3 and 25. The relative humidity is maintained between 54.3% and 59.8%. Also, these outcomes have indirectly promoted an average increase of 22.6% in the thermal comfort satisfactory level of the occupants. Practical application: The new conclusions from the simplified thermostat control strategy, which can be customised according to the environment variables in the air-conditioned space (in this case the operative temperature and the relative humidity) or based on the preferences of the occupants, such as the level of thermal comfort that suits the current thermal environment in tropical climates, could be applied as an important guide for building services engineers and researchers. Their aims are to reduce energy usage in HVAC systems in the non-green office buildings in tropical climates while maintaining an adequate thermal comfort level, and thus, the performance and well-being of the office workers are improved.